Pendampingan Pengukuran Kompetensi Membaca Kitab Kuning Melalui Sistem Akselerasi Al-Miftah Lil Ulum - Rifki, Abdurrahman; Edy Sulaiman; Anisah Isnaini; M. Mansyur (STAI Ma'had Aly Al-Hikam Malang, 2024)
Abstract Al-Miftah Lil Ulum is an Arabic language learning strategy that takes into account its principles, including nahwu and shorof, which is packaged pragmatically and delivered in a very interesting way. The Toronan Bere' Leke Islamic Boarding School includes learning the book Al-Miftah Lil Ulum as one of the mandatory subjects taught at the Islamic boarding school. So it is important to carry out this service with the aim of measuring the level of reading ability of students through the Acceleration model in al-Miftah lil Ulum. The service method used is the incandescent model which consists of planning, implementation and follow-up stages. The results of the service show that measuring the level of reading ability using the acceleration system was successfully carried out through two test stages, namely an oral test and a written test. From these two models, information was obtained that the ability to read the Yellow Book of Bere' Leke students is at a sufficient level. Keywords: Reading Ability, Yellow Book, Competency, Acceleration System. Abstrak Al- Miftah Lil Ulum merupakan suatu strategi pembelajaran bahasa Arab dengan memperhatikan prinsip-prinsipnya, termasuk nahwu dan shorof yang dikemas secara pragmatis dan disampaikan dengan cara yang sangat menarik. Pondok Pesantren Toronan Bere’ Leke memasukan pembelajaran kitab Al-Miftah Lil Ulum sebagai salah satu mata pelajaran wajib yang diajarkan di pesantren. Sehingga penting dilakukan pengabdian ini dengan tujuan mengukur tingkat kemampuan membaca santri melalui model Akselerasi pada al-Miftah lil Ulum. Metode pengabdian yang digunakan adalah model pijar yang terdiri dari tahapan perencanaan, pelaksanaan dan tindak lanjut. Hasil pengabdian menunjukan bahwasanya pengukuran tingkat kemampuan membaca dengan menggunakan sistem akselerasi berhasil dilakukan melalui dua tahapan tes yaitu tes lisan dan tes tulis. Dari dua model tersebut, didapatkan informasi bahwasanya kemampuan membaca kitab kuning santri bere’ leke berada pada tingkatan cukup. Kata Kunci: Kemampuan Membaca, Kitab Kuning, Kompetensi, Sistem Akselerasi.